2009
DOI: 10.1021/nl903409x
|View full text |Cite
|
Sign up to set email alerts
|

Metal Nanoparticles with Gain toward Single-Molecule Detection by Surface-Enhanced Raman Scattering

Abstract: Single-molecule detection via surface-enhanced Raman scattering (SERS) has raised great interest over the past decade. The usual approach toward this goal is to harness the strong surface plasmon resonance of light with complex metallic nanostructures, such as particle aggregates, two-particle gaps, sharp tips, or particles with sharp apexes. Here we propose another route toward the goal by introducing gain medium into single metal nanoparticles with simple geometry. Our calculations show that cubic gold nanob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
223
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(224 citation statements)
references
References 30 publications
0
223
1
Order By: Relevance
“…Several groups reported that the great SERS enhancement factor led to signals at levels similar to or better than those generated from fluorescence. 27,29,33 Second, Raman produces vibrational spectral bands with narrow line widths (∼1 nm), 34 and fluorescent bands can be as wide as 50 nm; 35 thus, Raman-based probes are inherently suitable for advanced multiplex analysis. Third, the extremely short lifetimes of Raman scattering prevent photobleaching, energy transfer, or quenching of reporters in the excited state, 36 rendering high photostability to SERS tags.…”
Section: Optical Properties Of Sers Tagsmentioning
confidence: 99%
“…Several groups reported that the great SERS enhancement factor led to signals at levels similar to or better than those generated from fluorescence. 27,29,33 Second, Raman produces vibrational spectral bands with narrow line widths (∼1 nm), 34 and fluorescent bands can be as wide as 50 nm; 35 thus, Raman-based probes are inherently suitable for advanced multiplex analysis. Third, the extremely short lifetimes of Raman scattering prevent photobleaching, energy transfer, or quenching of reporters in the excited state, 36 rendering high photostability to SERS tags.…”
Section: Optical Properties Of Sers Tagsmentioning
confidence: 99%
“…The recently developed plasmon lasers showed that these dampings can be fully compensated by gain medium at the lasing state [27][28][29][30][31][32][33][34][35][36][37][38]. This intrinsic merit has great potential to enhance the performance of devices based on plasmonic resonance phenomena [39][40][41][42][43][44][45]. One example is the plasmon laser for gas phase detection where the mechanism of the sensing process relies on surface defect state modification of semiconductor material [46].…”
mentioning
confidence: 99%
“…The lower noise-signal ratio may be the result of the larger absorption loss for gold material in the near infrared, the higher absorption loss produces much quicker decay in surface plasmon resonance and shorter life expectancy. As the electric field strength is proportional to the accumulation of incident energy, shorter life means the shorter accumulation time, less energy, lower intensity [9], and the local electric field and SERS enhancement factor is also small, which means weaker Raman signals. …”
Section: Resultsmentioning
confidence: 99%